2018
DOI: 10.1073/pnas.1720716115
|View full text |Cite
|
Sign up to set email alerts
|

Maize yields over Europe may increase in spite of climate change, with an appropriate use of the genetic variability of flowering time

Abstract: SignificanceThe consequences of climate change on European maize yields may become positive if farmers in 2050 use the decision rules they currently follow for adapting plant cycle duration and sowing dates to the diversity of environmental conditions. Experiments and simulations show that the current genetic variability of flowering time allows identifying a cycle duration that maximizes yield at every maize field in Europe. The assumption that farmers use this optimal cycle length in each site was supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 38 publications
8
105
0
Order By: Relevance
“…As such, selecting cultivars that maintain the original growing period under warming is a viable adaptation measure in most regions, as it reduces or fully compensates negative effects of warming on crop yields. This confirms recent findings in that historical warming already leads to the use of longer maturing cultivars, which in turn contributed to the increasing yield trend in the United States and Europe (Butler et al, ; Parent et al, ). The response, however, is variable across regions, crops, and GGCMs and thus subject to uncertainties.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As such, selecting cultivars that maintain the original growing period under warming is a viable adaptation measure in most regions, as it reduces or fully compensates negative effects of warming on crop yields. This confirms recent findings in that historical warming already leads to the use of longer maturing cultivars, which in turn contributed to the increasing yield trend in the United States and Europe (Butler et al, ; Parent et al, ). The response, however, is variable across regions, crops, and GGCMs and thus subject to uncertainties.…”
Section: Discussionsupporting
confidence: 89%
“…Different agronomic management options have been proposed as adaptation strategies against temperature‐induced yield losses. Most commonly, these include a shift of sowing dates, choice of cultivars with adjusted phenology, and irrigation (Challinor et al, ; Olesen et al, ; Parent et al, ; Ruiz‐Ramos et al, ; Semenov et al, ; Tack et al, ). Sowing dates can be advanced or delayed to match the most favorable thermal conditions and to exploit a longer growing season (Olesen et al, ; Sacks et al, ; Waha et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, Parent et al (2018) used experiments and a process-based model to analysis the results of climate change on European maize yields under the farmers who used the best current genetic variability. The results showed that if the crop cycle was adapted, the total maize yield increased by 4.5% and 7.0% for RCP (Representative Concentration Pathways) 4.5 and 8.5, respectively, under a moderate increase in transpiration efficiency (TE) [19]. Among many management practices, optimizing the sowing dates of crop was considered to be another efficient way to avoid heat/drought stress on phenology development or a reduction in crop yield.…”
mentioning
confidence: 99%